Preconditioning activities to enhance repeated high-intensity efforts in elite rugby union players - Vachon, A.; Berryman, N.; Mujika, I.; Paquet, J.; Bosquet, L. (International Journal of Sports Physiology and Performance, 2022)
Purpose:To assess the effect of a rugby-specific high-intensity interval-training (HIITRugby) protocol on the repeated high-intensity-effort ability of young elite rugby union players and to verify the influence of 2 preconditioning sequences composed either of physical contacts (ie, tackles) or of additional runs on the magnitude of improvement. Method: Fourteen players (19 [1] y; 183.5 [8.6] cm; 95.6 [15.6] kg) underwent an HIITRugby protocol, consisting of 7 supervised training sessions over 4 weeks, each session including 3 or 4 sets of 1 to 2 minutes with 1-minute recovery. Prior to HIITRugby training, players underwent a preconditioning contact sequence or a preconditioning running sequence, to assess their influence on subsequent interval-training sessions. Results: The overall group showed a moderate improvement in total sprint time, sprints =90% of the best, and 20-m sprint (-3.91% [2.68%], P = .0002; 74.6% [123.7%], P = .012; -3.22% [3.13%], P = .003, respectively) and a large improvement in percentage decrement (-23.1% [20.5%], P = .005) following the 4-week training block. Relative improvements were similar between groups in total sprint time, 20-m sprint, and perceived difficulty, but the preconditioning running-sequence group exhibited a larger magnitude of gains in percentage decrement (-28.6% [20.2%] vs -17.6% [20.7%]; effect size = -1.01 vs -0.73). Conclusion: An HIITRugby training block was effective to improve repeated high-intensity-effort ability. A preconditioning contact sequence prior to HIITRugby can reduce subsequent long-interval running activity, which may attenuate the improvement of repeated high-intensity-effort indices related to the aerobic system.